Afghanistan : Report on Observance of Standards and Codes - Accounting and Auditing - World Bank (World Bank, 2012)
This report is based on a review of the strengths and weaknesses of corporate accounting and auditing practices in Afghanistan. It forms part of a joint initiative between the World Bank and the International Monetary Fund (IMF) on Reports on the Observance of Standards and Codes (ROSC), which covers a set of twelve internationally recognized core standards and codes relevant to economic stability and private and financial sector development. The review involved the assessment of actual practices and an analysis of the effectiveness of monitoring and enforcement mechanisms, in the area of corporate accounting and auditing in Afghanistan. International Financial Reporting Standards (IFRS) and International Standards on Auditing (ISA) served as benchmarks for evaluating comparability of locally applicable accounting and auditing requirements. The review used a diagnostic template developed by the World Bank to facilitate collection of information. The information was complemented by the findings of a due diligence exercise, based on a series of meetings with key stakeholders, conducted by World Bank staff and consultants.